Effect Of NPK Fertilizer and Chitosan on Growth and Production of Green Mustard (Brassica juncea L) - Samsul B. Letahiit; Maria Nindatu; Cecilia A. Seumahu; Johan Riry (Faculty of Agriculture, Pattimura University, 2022)
The decline of mustard (Brassica juncea L.) production can indicate a plant nutrition problem. The purpose of this pot experiment was to determine the response of green mustard to the application of NPK and Chitosan fertilizers which were applied at the same time. The experimental design completely randomized design with three replications and two factors, namely NPK fertilizer with five levels of dosage, namely 0.0 g/plant, 0.4 g/plant, 0.8 g/plant, 1.2 g/plant, and 1.6 g/plant, and Chitosan with four levels of concentration, namely: 0%, 10%, 20% and 30%. Observed variables were plant height, number of leaves, average leaf area, total leaf area, root length, root fresh weight, stem diameter, and plant fresh weight. The results of the study found that the use of NPK and Chitosan fertilizers increased plant growth indicated by plant height, number of leaves, leaf area and root length, as well as plant yield indicated by plant fresh weight. There was no interaction effect between the two treatments but independently both treatments have a positive effect on growth and yield of green mustard. The higher the dose of NPK fertilizer and the concentration of chitosan will increase the effect. The best treatment composition recommended for green mustard cultivation was NPK fertilizer with a dose of 1.6 g/plant and chitosan with a concentration of 20%.